2010
DOI: 10.1021/ja1022128
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the LSPR Spectral Overlap for Energy Transfer between a Dye and Au Nanoparticle

Abstract: Nanometal surface energy transfer (NSET) is a molecular ruler technique that has been utilized to optically probe long distances in biomolecular structures. We investigate the useful spectral range of donor dyes and the importance of overlap between the localized surface plasmon resonance (LSPR) and the donor photoluminescence (520-780 nm) and provide a comprehensive study of the R(0) values for the NSET processes from dyes to 2 nm Au NP (gold nanoparticle). The distance-dependent quenching results provide exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
256
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(262 citation statements)
references
References 65 publications
5
256
1
Order By: Relevance
“…[18][19][20][21][22][23] The interaction of emitters with metallic nanospheres has been extensively studied, both theoretically [24][25][26][27][28][29][30][31][32][33][34][35][36] and experimentally. [37][38][39][40][41][42][43][44][45][46][47][48][49] There have been reports using different metallic NP size regimes and a variety of quantum dot and dye fluorophores. In Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22][23] The interaction of emitters with metallic nanospheres has been extensively studied, both theoretically [24][25][26][27][28][29][30][31][32][33][34][35][36] and experimentally. [37][38][39][40][41][42][43][44][45][46][47][48][49] There have been reports using different metallic NP size regimes and a variety of quantum dot and dye fluorophores. In Refs.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that experiments probing the spectral dependence by varying the quantum emitter wavelength are also susceptible to changes in the quantum yield. 41,45,46 The interaction between a quantum emitter and a metallic NP has also attracted theoretical interest, with both large and small NP considered. Anger et al reported an experimental and theoretical study of the change in the radiative and non-radiative rates of a single quantum emitter as a function of its separation from an 80 nm diameter Au NP, 24 whereas Carminati et al considered smaller Ag NP with a radius of 5 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The key differences are that FRET is a dipole-dipole type energy transfer with 1∕r 6 distance dependence, while NSET is a dipole-surface type energy transfer following 1∕r 4 distance dependence. [83][84][85] This sensor was very sensitive with a detection limit of 0.4 and 1.2 ppb toward Hg 2þ in the buffer solution and in the river water, respectively, values which satisfactorily meet the sensitive demands of U.S. Environmental Protection Agency (EPA) and World Health Organization (WHO).…”
Section: Nucleic Acidsmentioning
confidence: 75%
“…The fluorescence quenching of fluorophore can be explained like the Förster energy transfer between two fuorophores that makes the fluorescence of the donor decrease. This energy transfer can be attributed to the surface energy transfer mechanism (SET) [17][18][19][20]. To investigate the recombination rates in the cases of enhancement and quenching fluorescence, the lifetime and quantum yield of the OBs solution with the presence of GNPs have been measured.…”
Section: Resultsmentioning
confidence: 99%